Από τα συμβάντα του λόγου στην εγκύκλιο γνώση - Ζαβιτσάνου, Ιόλη (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Αρχιτεκτόνων Μηχανικών, 2014)
This thesis aims to investigate the ratio of interwar modernistic speech, especially that of Le Corbusier through the manifesto Toward an Architecture. The investigation is carried out through the parallel reading with the literary work Impressions d’ Afrique of Raymond Roussel and by using as a theoretical tool the philosophical theory of Alain Badiou for the event and truth. Considering that the text of Roussel can serve as an example illustration of the route of truth, it is used as a deduction method for the study of the stages of truth path in Le Corbusier’ s, work claiming the total power of truth implies the disaster the third name of Evil, as defined by Alain Badiou. Every step in building up the sheer truth is detected initially in the text of Roussel and then in Le Corbusier’ s text, which means the event, the subjective formulation and the generic truth. So three dipoles, which are based on Badiou theory are applied on the texts. Analyzing one pole, you are given a description of the other, while deepening into their differences allows detection of the point at which Toward an Architecture embodies the criterion of disaster. Concluding, the thesis attempts to display an identification tool of evil, to give an outlining deduction of mental instruments for figuring out the signs and features of Evil as they were shaped by parallel reading of the two texts. Thus, these conclusions can be generalized.